The issue of the impact of lexical-semantic changes on socio-cultural communication - Aminova , Khalima Akobir qizi; Bakhronova , Dilrabo Keldiyorovna (The Lingua Spectrum, 2026)
This article examines lexical-semantic transformations that emerged during the COVID-19 pandemic through the lens of socio-cultural communication. The study analyzes the linguocultural function of the war metaphor in pandemic discourse, the phenomenon of virus personification, and the semantic reinterpretation of the concept of “freedom.” The article investigates slogans, symbolic syntagms, and emotionally charged discursive tools employed in Uzbekistan and international public communication. Furthermore, it explores alternative discourses opposing official narratives, including political opposition speech, denialist (negationist) rhetoric, and the phenomenon of fake news from a linguistic perspective. The research draws on corpus-based and discourse analysis methods to examine how pandemic language functioned as an ideological and emotional tool in public communication. The findings demonstrate that pandemic lexicon transcended the boundaries of medical terminology, evolving into a linguocultural phenomenon encoding social psychology, political ideology, and cultural values. Pandemic language has formed a complex semantic system reflecting collective emotions such as fear, solidarity, responsibility, and hope within society.